Penguatan literasi lingkungan melalui kegiatan Hidroponik untuk membangun Green School di SDU Hamzanwadi - Mijahamuddin Alwi; Musabihatul Kudsiah; Arif Rahman Hakim; Burhanuddin Burhanuddin; Donna Boedi Maritasari (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Environmental literacy is a part of education that helps students protect the environment by using or consuming nature and by understanding and solving environmental problems caused by actions that exploit the natural environment, forests, and other natural resources in the area. This activity tries to teach people more about the environment by growing hydroponically grown vegetables in the school to make the school a healthier and cleaner place. SDU Hamzanwadi has never enhanced environmental literacy through hydroponic activities; therefore, this should advance environmental preservation awareness. The method is implemented in three stages: 1) the planning stage includes field surveys, cooperation, and communication; 2) the implementation stage includes socialization and mentoring by the Lecturer Team in collaboration with Hamzanwadi University PGSD Students; 3) the monitoring and evaluation stage. The survey findings were shared with school partners, beginning with the principal and teachers. Then, an agreement is drafted pertinent to the school's conditions, notably hydroponics production. The outcomes of the activity demonstrated that 90% of the participants were able to conduct hydroponics directly. Some participants' mastery and comprehension reached 85%, and they could utilize the help material that had been developed. This is evident in the enhanced knowledge and abilities of the partners, as seen by the green and healthy plants. The production of hydroponics necessitates considerable skill and knowledge as well as a sizeable financial investment. Thus, careful planning is required. Hydroponics is not only an educational tool for environmental literacy but may also beautify and green the school environment.